The phenomenology of psilocybin: transformative insights for research and clinical practice - Metastasio, Antonio; Prevete, Elisabeth; Venturini, Sofia; Garofalo, Andrea; Cecconello, Beatrice; De Pisapia, Nicola; Corazza, Ornella (Frontiers in Psychology, 2025)
IntroductionConsidering the increasing evidence supporting psilocybin’s efficacy in therapeutic settings, it is essential to deepen our understanding of its subjective meanings and effects to enhance its integration into psychotherapy. Current knowledge is primarily based on psychometric assessments or unstructured personal reports, leaving a gap in the qualitative analysis of subjective psychedelic experiences and the resulting changes.ObjectiveThis study aimed to describe the subjective psychedelic experience with psilocybin in a structured, objective, and non-judgmental way (Epoche), while exploring its potential clinical applications.MethodsA phenomenological qualitative approach, integrating interpretative phenomenological analysis (IPA) and the dynamic analysis (PHD) method, was used to analyze self-reported psilocybin experiences. Participants who met the inclusion criteria of being healthy adults and who had experienced psilocybin without any other substances were recruited through convenience sampling. Semi-structured interviews explored dimensions such as emotions, bodily sensations, perception of time and space, relationships, values, and enduring transformation. Data were analyzed using thematic coding.ResultsTen interviews were carried out with voluntary participants. All the interviewees reported enhanced emotional and interpersonal sensitivity, increased empathy, a deeper connection to others, and a heightened ability to resolve personal issues as well as long-lasting insights into their lives and values. Participants also showed profound changes in behavior, attitudes, and interests, indicative of the potential for psilocybin to catalyze significant personal growth and development.ConclusionThis study highlights the transformative potential of psilocybin experiences and their relevance to psychotherapeutic practices. By employing phenomenological methods, we offer a structured understanding of these states, which could be used in future to provide guidance for their integration into therapy by giving a better insight into psychedelic experience.